PENGARUH TUMBUHAN KABOMBA (Cabomba aquatica Aubl.) TERHADAP KADAR TSS, DO dan COD LIMBAH CAIR LABORATORIUM KIMIA FMIPA UNTAN - Afriza, Hanafi; Mukarlina, Mukarlina; Rousdy, Diah Wulandari (Universitas Tanjungpura, 2019)
Laboratory is one of the producers of waste water with a high content of hazardous materials before being discharged into water bodies. One effort to process laboratory waste with phytoremediation is to use Kabomba plants (Cabomba aquatica Aubl). This study aims to determine the ability of Kabomba (Cabomba aquatica Aubl.) To see the influence of plants on the levels of Total Suspended Solid (TSS), Dissolved Oksigen (DO) and Chemical Oxygen Demand (COD) from the Untreated Chemistry Laboratory Liquid Waste of FMIPA. This study used a Completely Randomized Design consisting of five treatments of waste concentration: control, 25, 50, 75, 100%. Based on the results of the study, Cabomba plants (Cabomba aquatica, Aubl.) able to reduce TSS values by 37.67% and increase DO values by a percentage of 77.5% on day 5 of treatment but not yet able to reduce COD values and increase pH values.